Exploration of neurometabolic alterations in adolescent patients with bipolar depression and non-suicidal self-injury based on proton magnetic resonance spectroscopy - Wang, Chengji; Qu, Yuan; Shen, Xiaoqin; Tang, Xiaoxiao; Tong, Gaiyu; Wati, Meier; Naibi, Manzeremu; Zhang, Cheng; Zou, Shaohong (Frontiers in Psychiatry, 2025)
BackgroundAdolescent bipolar depression (ABD) refers to depressive episodes that arise in adolescent patients with bipolar disorder. Its identification and diagnosis are challenging, and it is characterized by a high rate of misdiagnosis and disability. Studies have revealed that patients with ABD are more prone to non-suicidal self-injury (NSSI) compared to those with unipolar depression. However, the neuropathophysiological mechanisms behind NSSI in ABD remain unclear. Therefore, this study employed proton magnetic resonance spectroscopy (1H-MRS) technology to investigate the potential relationship between NSSI and neurometabolism in the ventromedial prefrontal cortex (vmPFC) of patients with ABD.MethodsThis study compared brain biochemical metabolism between ABD with and without NSSI. Forty ABD were recruited and divided into groups with (n=21) and without NSSI (n=19). Proton magnetic resonance spectroscopy (1H-MRS) was used to detect the ratio of biochemical metabolites in the ventromedial prefrontal cortex (vmPFC) of all patients.ResultsThere was no statistically significant difference (P>0.05) in the age, gender, only child status, residential status, education level, age of onset, disease course, family history, and 24-item Hamilton Depression Scale (HAMD) score between patients in the NSSI group and those without NSSI group. The N-acetylaspartate (NAA)/creatine (Cr) of patients with NSSI was lower than that of patients without NSSI, and the difference was statistically significant (Z=-4.347,P<0.001). There was no statistically significant difference in choline (Cho)/Cr and myo-inositol (mI)/Cr between the group with NSSI and the group without NSSI (P>0.05).There is a positive correlation (r=0.703,P<0.00625) between Cho/Cr and HAMD scores in patients with NSSI, while there is a varying degree of negative correlation (r=-0.605,P=0.006;r=0.624,P=0.004) between mI/Cr and age and onset age in patients without NSSI. There is no correlation (P>0.05) between other indicators.ConclusionCompared with ABD without NSSI, ABD with NSSI have reduced NAA/Cr metabolism in the vmPFC brain area. The level of membrane phospholipid breakdown metabolism in the vmPFC brain area of ABD with NSSI may be related to the severity of depression. The level of phosphoinositol cycle in the vmPFC brain area of ABD without NSSI may be related to age or onset age. Therefore, further validation was required.